Analisis perencanaan, pelaksanaan, penatausahaan, pelaporan dan pertanggungjawaban pengelolaan keuangan desa Di Desa Kiawa Satu Utara Kecamatan Kawangkoan Utara - Singon, Dewita Sophia; Walandouw, Stanley Kho; Kindangen, Wulan D. (Riset Akuntansi dan Portofolio Investasi, 2025)
Village financial management encompasses a series of activities including planning, implementation, administration, reporting, and accountability. The substantial amount of village funds allocated by the central government presents potential risks for financial mismanagement, thereby necessitating orderly and procedural management. This study aims to analyze the stages of village financial management: planning, implementation, administration, reporting, and accountability in Kiawa Satu Utara Village. This research employs a descriptive qualitative method with data collected through observation, interviews, and documentation. Data were analyzed through a process of data collection, reduction, presentation, and drawing conclusions. The findings reveal that the planning, implementation, and accountability stages have been conducted in accordance with Minister of Home Affairs Regulation Number 20 of 2018. However, the administration and reporting stages have not been fully implemented in line with the applicable regulations.